Sympathetic neurotransmitters promote the process of recellularization in decellularized liver matrix via activating the IL-6/Stat3 pathway. (4th November 2016) - Wen, Xudong; Huan, Hongbo; Wang, Xiaojun; Chen, Xuejiao; Wu, Lili; Zhang, Yujun; Liu, Weihui; Bie, Ping; Xia, Feng
Abstract: Recellularized liver, as an approach for hepatic tissue engineering, is an effective alternative to orthotopic liver transplantation for end-stage hepatic failure. When compared with normal liver, recellularized liver has a disparity in hepatocyte viability and function, owing to the difficulty of fully simulating the microenvironment of liver. Although the sympathetic nervous system (SNS) is considered an important constituent of liver function, few studies have examined the effect of the SNS on hepatic tissue engineering. It is imperative to explore the regulation of the SNS on a tissue-like configuration to obtain an intact recellularized liver with better hepatic function. We have observed that various subtypes of adrenergic receptors (ARs) are expressed on the hepatocyte membrane. Salbutamol, an agonist of β 2-AR, promoted cell proliferation, albumin secretion and urea synthesis in the recellularized liver. Cytokines were screened in isoprenaline/salbutamol-treated recellularized liver, and the expression of IL-6 was significantly increased. Isoprenaline or salbutamol especially promoted the expression of Stat 3 and phosphorylated Stat 3, contributing to the activation of IL-6/Stat 3 signalling in promoting hepatocyte proliferation and recellularized liver function. This study suggests that activation of β 2-AR accelerated hepatocyte proliferation and improved recellularized liver function by mediating the IL-6/Stat 3 signalling pathway, indicating that nervous system regulation may be an essential component contributing to the complexity of recellularized liver in tissue engineering.